Engineering mechanics : dynamics - Pytel, Andrew; Kiusalaas, Jaan (Boston, Massachusetts : Cengage Learning Asia Pte Ltd, 2017)
Contaiins large number of problems that are to be solved by the student.
Introduction to dynamics -- Dynamics of a particle: rectangular coordinates -- Dynamics of a particle: curvilinear coordinates -- Work-energy with impulse-momentum principles for a particle -- Dynamics of particle systems -- Planar kinematics of rigid bodies -- Planar kinetics of rigid bodies: force-mass-acceleration method -- Planar kinetics of rigid bodies: work-energy and impulse-momentum methods -- Rigid-body dynamics in three dimensions -- Vibrations -- Proof of the relative velocity equation for rigid-body motion -- Numerical solution of differential equations -- Mass moments and products of inertia.
Includes index.
Keywords: DYNAMICS